Pengaruh Creativity, Self-Efficacy, Personal Innovativeness, dan Facilitating Conditions Terhadap Digital Entrepreneurial Intention pada Generasi Z di Kota Jakarta - Ahmad Salahudin; Terrylina Arvinta Monoarfa; Bagus Kharismawan (Indo Publishing, 2026)
Unemployment among Generation Z remains a serious issue, particularly in urban areas such as Jakarta. The rapid development of digital technology offers alternative opportunities through digital entrepreneurship; however, Generation Z’s intention to engage in digital entrepreneurship remains relatively low. This study aims to examine the influence of creativity, self-efficacy, personal innovativeness, and facilitating conditions on digital entrepreneurial intention among Generation Z in Jakarta. This study employed a quantitative approach using a survey research method. The research sample consisted of Generation Z individuals residing in Jakarta and was selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that creativity, self-efficacy, and facilitating conditions have a positive and significant effect on digital entrepreneurial intention, while personal innovativeness has no significant effect. These findings suggest that digital entrepreneurial intention among Generation Z is more strongly influenced by psychological factors, such as creativity and self-confidence, as well as by supportive digital environments, rather than by individuals’ tendencies to adopt new technologies. This study is expected to serve as a reference for educational institutions and policymakers in designing more effective digital entrepreneurship development strategies for Generation Z.